Image Steganalysis Using Image Quality Metrics (Structural Contents Metric) - Kahdum, A. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new method presented in this work to detect the existence of hiddendata as a secret message in images. This method must be applyied only on images which have the same visible properties (similar in perspective) where the human eyes cannot detect the difference between them.This method is based on Image Quality Metrics (Structural ContentsMetric), which means the comparison between the original images and stego images, and determines the size ofthe hidden data. We applied the method to four different images, we detect by this method the hidden data and  find exactly the same size of the hidden data.